Data Mining - Aggarwal, Charu C. (Springer, 2015)
The field of data mining has seen rapid strides over the past two decades, especially from the perspective of the computer science community. While data analysis has been studied extensively in the conventional field of probability and statistics, data mining is a term coined by the computer science-oriented community. For computer scientists, issues such as scalability, usability, and computational implementation are extremely important. The emergence of data science as a discipline requires the development of a book that goes beyond the traditional focus of books on only the fundamental data mining courses. Recent years have seen the emergence of the job description of “data scientists,” who try to glean knowledge from vast amounts of data. In typical applications, the data types are so heterogeneous and diverse that the fundamental methods discussed for a multidimensional data type may not be effective. Therefore, more emphasis needs to be placed on the different data types and the applications that arise in the context of these different data types. A comprehensive data mining book must explore the different aspects of data mining, starting from the fundamentals, and then explore the complex data types, and their relationships with the fundamental techniques. While fundamental techniques form an excellent basis for the further study of data mining, they do not provide a complete picture of the true complexity of data analysis. This book studies these advanced topics without compromising the presentation of fundamental methods. Therefore, this book may be used for both introductory and advanced data mining courses. Until now, no single book has addressed all these topics in a comprehensive and integrated way. The textbook assumes a basic knowledge of probability, statistics, and linear algebra, which is taught in most undergraduate curricula of science and engineering disciplines. Therefore, the book can also be used by industrial practitioners, who have a working knowledge of these basic skills. While stronger mathematical background is helpful for the more advanced chapters, it is not a prerequisite. Special chapters are also devoted to different aspects of data mining, such as text data, time-series data, discrete sequences, and graphs. This kind of specialized treatment is intended to capture the wide diversity of problem domains in which a data mining problem might arise.